2006
DOI: 10.1080/00933104.2006.10473313
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Social Studies Curriculum in the Context of Globalization: Education for Global Citizenship in the U.S.

Abstract: Scholarship on globalization suggests that new forms of democratic citizenship and politics are emerging, yet the U.S. educational system remains resistant to global perspectives in the curriculum and continues to favors national identity and patriotism over learning about the world. A national approach to citizenship, which is the norm in U.S. social studies classrooms, is unable to explain the complexity of global issues and their impact on students' lives. The argument is made that a new orientation to soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 32 publications
5
100
0
5
Order By: Relevance
“…They also mentioned discussing environmental and economic issues. The issues raised here are in line with Hanvey (1976) perspective of awareness of human choices which Myers (2006) would classify under the world systems approach which focuses on the interdependent nature of states around the world. They felt that these issues were important in that they are happening around them and may as well happen to them.…”
Section: Rq1: Teaching About World Issuessupporting
confidence: 55%
See 4 more Smart Citations
“…They also mentioned discussing environmental and economic issues. The issues raised here are in line with Hanvey (1976) perspective of awareness of human choices which Myers (2006) would classify under the world systems approach which focuses on the interdependent nature of states around the world. They felt that these issues were important in that they are happening around them and may as well happen to them.…”
Section: Rq1: Teaching About World Issuessupporting
confidence: 55%
“…In another study, Merryfield (2000) findings revealed some deficiencies in teacher education programs that teachers are not being prepared to teach for diversity, equity and interconnectedness, noting that the question of why teacher education is not preparing teachers well will continue to dominate the discussions in teacher education. Myers (2006) opines that although there is some consistency in the basic principles that underpin teaching about the world, there are diverse ideological approaches to teaching about the world in terms of goals and curriculum themes. Three approaches to teaching about the world identified are: international business training, international studies, and world system approach (Myers, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations